FULL E-BOOK INDONESIAN LAW JOURNAL VOLUME 18 N0. 1, 2025 - Afifah Salwa, Nabila; Siagian, Fahrizal S.; Rosmalinda; Hanifah Azizah; Meirani Rubianto; Angkawidjaja, Elizabeth Vania; Wijaya, Emilia Metta Karunia; Fikri Triandhika; Lies Sulistiani; Iswara, Rizka; Andriamaharitra, Paul Alberti (Badan Pembinaan Hukum Nasional Kementerian Hukum Republik Indonesia, 2025)
The 2025's first edition of Indonesian Law Journal Volume 18 has been published. The discussion topic of this edition is Sexual Offending and The Law. This edition presents 5 (five) articles from authors with various backgrounds. Please enjoy reading as we hope these article in our Journal are beneficial and constructive towards the development of national law